Exploring antecedents of responsible consumption using structural equation modeling - Jain, Vijay Kumar; Chamola, Pankaj (Serbian Journal of Management, 2019)
The perennial use of resources due to excess consumption has endangered the environment and is a grave concern for all of us. The current rate of resource consumption may deprive the future generation from the resources that we have been enjoying. The conservation of these resources for long requires judicious and rational consumption practices from consumers. Therefore, responsible consumption is need of hour to further prevent environmental degradation and resources depletion. This paper aims to explore the antecedents of responsible consumption. A theoretical model was developed to explain and empirically verify the antecedents of responsible consumption. Four antecedents namely environmental education, perception of fair trade, taxation and neuroticism have been taken as exogenous variables. The model was tested and statistically validated using structural equation modeling relying on data collected through 300 respondents. The environmental education has emerged as the most important antecedent of responsible consumption followed by taxation, perception of fair trade and neuroticism respectively. The finding of the study would contribute towards enhancing responsible and judicious use of resources, thereby, reducing consumption and improving environment.